2014
DOI: 10.1002/tea.21156
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of learning progressions in two teacher communities

Abstract: Learning progressions, or sequences of how ideas and practices develop within domains, are increasingly a focus of science education research. Recently, researchers have called for these progressions to be used as interpretive frameworks for teachers' instructional planning and assessment practices. In this study, we explore data from two high schools collected in two studies. In the first study, we engaged with teachers to develop and refine a learning progression for natural selection alongside formative ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
76
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 50 publications
0
76
0
5
Order By: Relevance
“…The concentration of the present study on learning products wishes to underscore the importance of formative assessment for aligning curricula, instruction, and assessment in LPs (e.g., Duschl et al, ; Furtak & Heredia, ; Lehrer & Schauble, ; Yin et al, ). Learning products could serve as templates to timely diagnose the distance of actual learner performance from optimal performance.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The concentration of the present study on learning products wishes to underscore the importance of formative assessment for aligning curricula, instruction, and assessment in LPs (e.g., Duschl et al, ; Furtak & Heredia, ; Lehrer & Schauble, ; Yin et al, ). Learning products could serve as templates to timely diagnose the distance of actual learner performance from optimal performance.…”
Section: Discussionmentioning
confidence: 94%
“…Further, pre‐post formats do not allow educators to offer support and guidance to learners as long as a learning activity sequence unfolds, whereby formative assessment would lose much of its practical use (Black et al, ; Briggs & Peck, ; Yin et al, ). Recent studies called for a thorough analysis of learner reasoning to diagnose learner performance and provide timely feedback to learners (Furtak & Heredia, ; Gunckel, Covitt, Salinas, & Anderson, ; Lehrer & Schauble, ). A third challenge for embedding formative assessments in LPs has been to identify proper timing for educators to intervene before moving forward (Lehrer & Schauble, ; Penuel, ; Yin et al, ).…”
mentioning
confidence: 99%
“…Understanding and using LPFs are challenging for teachers. Researchers found that, when using LPFs to interpret students’ thinking, teachers tend to take a fragmented view of student thinking (Alonzo & Elby, ) and treat students’ ideas as misconceptions to be corrected rather than resources for learning (Furtak & Heredia, ); when using LPFs to inform teaching, teachers often think of instructional strategies only at a very general level such as using more hands‐on activities (Alonzo & Elby, ; Jin et al, ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Some researchers have assessed learning outcomes of interventions that used learning progression‐based curriculum (Jin, Zhan, & Anderson, ; Plummer & Krajcik, ; Songer, Kelcey, & Gotwals, ). Others have studied teachers’ understanding of learning progressions (Jin, Shin, Johnson, Kim, & Anderson, ) and teachers’ use of learning progressions in planning and implementing lessons (Furtak, ; Furtak & Heredia, ). An introduction to the learning progression approach and examples of learning progression studies can be found in Barrett and Jin () and Stevens, Gotwals, Jin, and Barrett ().…”
mentioning
confidence: 99%
“…It consists of ordered levels, which are qualitative descriptions of observable student behaviors as thinking develops from intuitive (and sometimes problematic) ideas to conceptions that are increasingly advanced, nuanced, and precise (see Confrey, Maloney, Nguyen, Mojica, & Myers, ; Corcoran, Mosher, & Rogat, ; Deane, Sabatini, & O'Reilly, ; National Research Council, , ; Simon, ; Smith, Wiser, Anderson, Krajcik, & Coppola, ). Research on the development and validation of LPs is now widespread in the educational sciences (e.g., Alonzo & Gotwals, ; Black, Wilson, & Yao, ; Briggs & Peck, ; Graf & van Rijn, ; Steedle & Shavelson, ; van Rijn, Graf, & Deane, ; West et al, ; Wilmot, Schoenfeld, Wilson, Champney, & Zahner, ; Wilson, ), but there is relatively little research on how an important group of end users (teachers) interprets them for the purpose of assessing and guiding students (Furtak & Heredia, ). In the context of assessment, it cannot be assumed that all teachers (or all researchers) will interpret an LP in the same way, or in the way intended by the developers of the progression, and if they do not, the same student performance may be assigned to different levels of a progression by different users.…”
mentioning
confidence: 99%